Green GDP Accounting and Green Economic Efficiency Analysis in Yunnan Province under the Double Carbon Background: Based on the Three-Stage DEA-Malmquist Model - Liu, Qitao (International Journal of Global Economics and Management, 2023)
In the efforts to practice the dual carbon national strategic objectives under the premise, this paper takes Yunnan Province as the research object, firstly constructed the green GDP evaluation index system, on this basis, the use of entropy method to calculate the green GDP value and ECI index of Yunnan Province, the development of Yunnan Province on the economy and resources and environment between each other was briefly studied; then through the above data to further select the green economic efficiency input-output index application of three-stage DEA-Malmquist model of green total factor productivity in Yunnan Province to calculate and analyze, obtain the five-year green economic efficiency level of Yunnan Province; finally through a large number of data analysis of technical progress index is the most important factor affecting the green economic efficiency of Yunnan Province, and give appropriate countermeasures and suggestions.